Indian business understanding a rapidly emerging economy - Budhwar, Pawan S.; Varma, Arup; Kumar, Rajesh 1954- (Routledge, 2019)
The Indian economy is projected to become the world's fourth largest by 2020 and it is central to global economic performance. In a period of rapid change, understanding the business environment is a challenge. This book highlights the unique mix of challenges and opportunities for investors and organizations in India. Indian Business brings together a wide range of experts to present a comprehensive insight into doing business in India. It draws on research-based evidence and expert coverage of the emerging political, legal and social frameworks. It is divided into three parts: the Indian business context, conducting business in India, and emerging practices relevant for foreign investors. Each chapter outlines the context and justification for study, along with an analysis of the present situation and future options. Useful features include a case study with questions for analysis, and links to useful web resources. This book provides business practitioners and students with a thorough understanding of how to start and grow successful organizations in India